Survival and mortality from COVID-19 in Bogota, Colombia during march and july 2020 (Research, Society and Development, 2020)
Objective: To determine the survival rate of COVID-19 in Bogotá-Colombia between March and July 2020. Materials and Methods: a retrospective cohort study was made in a population infected by COVID-19 in Bogotá from March 6 to July 8, 2020. Incomplete data was excluded and data reported to the INS were used. Infected populations were confirmed via PCR test; the study time starts intiates during onset of symptoms until death or the final time of the cohort. For survival, the actuarial method, the Long-Rank test, was applied. Results: Survival rate on days 1, 10, 20 and 30, is of 100%, 99%, 98% and 96% respectively, (p